Penerapan Media Puzzle dalam Meningkatkan Kemampuan Mengenal Warna - Harmonis, Mistria (Lembaga Yasin AlSys, 2022)
This research is a descriptive qualitative research with the type of field study research, with the aim of this research being able to provide an overview of the use of puzzle media in learning to recognize colors in early childhood. This research was conducted at the Melati Muslimat PAUD institution which is located in the Village of Rawan Besuki Situbondo. The research was conducted for approximately 3 weeks using interview and observation techniques as data collection techniques. While the subjects in this study were the heads of institutions, teaching teachers and students. The results of the study say that the use of puzzle media in recognizing colors in Melati Muslimat PAUD can be said to be positive, with puzzle media it is easier for children to recognize and remember colors, besides that children also become more enthusiastic in participating in the teaching and learning process.